Nano magnetic sulfated zirconia (Fe3O4@ZrO2/SO42−): an efficient solid acid catalyst for the green synthesis of α-aminonitriles and imines. (2nd June 2015) - Ghafuri, Hossein; Rashidizadeh, Afsaneh; Ghorbani, Behnaz; Talebi, Majid
<x xml:space="preserve">Abstract</x> In this research, nano magnetic sulfated zirconia was prepared through a green and facile method and acted as a novel, heterogeneous, efficient nano-catalyst for the one-pot three component synthesis of α-aminonitrile derivatives.